2016
DOI: 10.22140/cpar.v7i1.98
|View full text |Cite
|
Sign up to set email alerts
|

If Only We Knew What We Know: Factors for Mobilizing Citizen Participation in Community-based Emergency Preparedness

Abstract: This study examines factors for mobilizing citizen participation in community-based emergency preparedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Hicks et al demonstrated that citizens' participation led to global mapping and resulted in enhancing the disaster reduction [6]. They showed how a real-time natural disaster In fact, when disaster strikes, because citizens are present at the scene of a disaster, they can be the "true" first responders, who can actively address community needs by participating in activities such as the restoration of public services and infrastructure [22][23][24][25][26][27]. Therefore, the government expects more efficient solutions by encouraging individuals to participate in disaster management.…”
Section: Introductionmentioning
confidence: 99%
“…Hicks et al demonstrated that citizens' participation led to global mapping and resulted in enhancing the disaster reduction [6]. They showed how a real-time natural disaster In fact, when disaster strikes, because citizens are present at the scene of a disaster, they can be the "true" first responders, who can actively address community needs by participating in activities such as the restoration of public services and infrastructure [22][23][24][25][26][27]. Therefore, the government expects more efficient solutions by encouraging individuals to participate in disaster management.…”
Section: Introductionmentioning
confidence: 99%
“…National and local government authorities perform a central role of networks and inter-connectivity established through an increasingly globalized economy [42] and their ability to communicate information to local citizens [43]. However, Schipper and Pelling [44] suggested that "DRR is largely a task for local actors, although with support from national and international organizations." This is because DRR policies and approaches consider a comprehensive view of risks and hazards, mostly socio-economic and political in origin since "wider social, political, environmental and economic environments in which a hazard is situated" [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Facing ever-changing and dynamic environments, network participants in the emergency management process create complex systems of disaster response [24]. Public agencies dominate disaster responses; however, they possess limited capacities and organizational fragility, which means they cannot solely manage emergency situations [25,26]. The enhancement of NPO engagement is the chief factor in developing community resilience because community-based NPOs assist in the delivery of accurate information, disseminate emergency messages, and offer emergency services to local residents [27,28].…”
Section: Enhancing Emergency Management Capacity For Governmentsmentioning
confidence: 99%
“…In terms of their roles, the Volunteer Firefighter Unit and Phoenix Volunteer Team offer immediate assistance when regional disasters occur, whereas the Women's Fire Prevention Promotion Team focuses on the implementation of emergency preparedness plans. Before disaster occurrence, they join disaster response exercises and plan and deliver disaster response information to the public, particularly imparting emergency-related knowledge and approaches to potential disaster responses [25].…”
Section: Main Types Of Emergency Npos In Taiwanmentioning
confidence: 99%